2022
DOI: 10.3390/biom12070979
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Gene Correlation Networks of Breast Cancer Patients Based on Mutations in TP53

Abstract: Breast cancer is one of the most prevalent cancers in females, with more than 450,000 deaths each year worldwide. Among the subtypes of breast cancer, basal-like breast cancer, also known as triple-negative breast cancer, shows the lowest survival rate and does not have effective treatments yet. Somatic mutations in the TP53 gene frequently occur across all breast cancer subtypes, but comparative analysis of gene correlations with respect to mutations in TP53 has not been done so far. The primary goal of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Multi-omics mutation analysis based on the CRRS model can identify specific genomic changes related to the circadian rhythm of BC, and could lead to more precise and individualized therapeutic strategies for patients with BC. Previous research has shown that somatic mutations are associated with poor outcomes in BC [ [53] , [54] , [55] , [56] ]. We investigated the differences in the distribution of somatic mutations between populations at different risk levels.…”
Section: Resultsmentioning
confidence: 99%
“…Multi-omics mutation analysis based on the CRRS model can identify specific genomic changes related to the circadian rhythm of BC, and could lead to more precise and individualized therapeutic strategies for patients with BC. Previous research has shown that somatic mutations are associated with poor outcomes in BC [ [53] , [54] , [55] , [56] ]. We investigated the differences in the distribution of somatic mutations between populations at different risk levels.…”
Section: Resultsmentioning
confidence: 99%
“…After statistically scoring the information of breast cancer genes as new key pathogenic genes, these genes were recommended as potential targets for clinical therapy. The authors of [70] also conducted a study to identify gene correlations between two groups of breast cancer patients and to derive potential prognostic gene pairs for breast cancer.…”
Section: Inherited Genementioning
confidence: 99%